Effects of non-invasive brain stimulation in multiple sclerosis: systematic review and meta-analysis. (February 2022) - Kan, Rebecca L.D.; Xu, Grace X.J.; Shu, Kate T.; Lai, Frank H.Y.; Kranz, Gottfried; Kranz, Georg S.
Objective: The objective of this meta-analysis was to summarize evidence on the therapeutic effects of non-invasive brain stimulation (NIBS) on core symptoms of multiple sclerosis (MS). Specifically, findings from studies deploying transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS) protocols were summarized in this review. Methods: We systematically searched articles published in four databases, until 31 May 2021, which compared the effects of active tDCS or rTMS with sham intervention in MS patients. We used a random-effects model for this meta-analysis. Meta-regression and subgroup meta-analysis were used to examine the effects of stimulation dose and different stimulation protocols, respectively. Results: Twenty-five randomized controlled trials (RCTs) were included in this review, consisting of 19 tDCS and 6 rTMS studies. tDCS led to a significant and immediate reduction of fatigue with a large effect size (Hedges's g  = −0.870, 95% confidence intervals (CI) = [−1.225 to −0.458], number needed to treat (NNT) = 2). Particularly, a subgroup analysis showed that applying tDCS over the left DLPFC and bilateral S1 led to fatigue reductions compared to sham stimulation. Furthermore, tDCS had favorable effects on fatigue in MS patients with low physical disability but not those with high physical disability, and additionally improved cognitive function. Finally, whereas rTMS was observed to reduce muscle spasticity, these NIBS protocols showed no further effect on MS-associated pain and mood symptoms. Conclusion: tDCS in MS alleviates fatigue and improves cognitive function whereas rTMS reduces muscle spasticity. More high-quality studies are needed to substantiate the therapeutic effects of different NIBS protocols in MS.